2011
DOI: 10.1021/ja207775a
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed C(sp3)–C(sp3) Bond Formation Using a Hypervalent Iodine Reagent: An Efficient Allylic Trifluoromethylation

Abstract: An efficient copper-catalyzed allylic trifluoromethylation reaction has been developed. This reaction provides a general and straightforward way to synthesize allylic trifluoromethylated compounds under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(183 citation statements)
references
References 61 publications
2
170
0
7
Order By: Relevance
“…In 2011, the groups of Buchwald 23 and Wang 24 showed that Togni's reagents can be used as a clean source of the CF 3 radical for the trifluoromethylation of alkenes. These trifluoromethylations rely on Cu(I) catalysis, and experimental evidence for the involvement of free CF 3 radicals was provided (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, the groups of Buchwald 23 and Wang 24 showed that Togni's reagents can be used as a clean source of the CF 3 radical for the trifluoromethylation of alkenes. These trifluoromethylations rely on Cu(I) catalysis, and experimental evidence for the involvement of free CF 3 radicals was provided (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…A proposed mechanism for this trifluoromethylation reaction is depicted in Scheme 3. Reaction of Togni's reagents with a copper catalyst generates a CF 3 radical (Scheme 2), 23,24 followed by radical addition and single-electron oxidation to give intermediate C. 26 Subsequent trapping of the carbocation C with a nucleophile leads to the desired product D. It is assumed that trifluoromethylation of olefin substrate E might be achieved using a copper-based strategy involving the generation of an allylic radical and a subsequent CF 3 transfer (Scheme 3, Path A). [27][28][29] Alternatively, if Togni's reagent 1 could be used as an electrophilic CF 3 ·equivalent, the final product F may be generated through an atom transfer radical addition type pathway (Scheme 3, Path B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Parsons et al, 84 Xu et al, 85 and Wang et al 86 reported the trifluoromethylation of unactivated olefins with a copper(I) salt and either Umemoto or Togni reagent ( Figure 39). Although these reactions provide accesses to compounds bearing CF 3 at allylic positions, these transformations are restricted to monosubstituted terminal olefins.…”
Section: Synthesis Of Alkenyl and Alkyl Trifluoridesmentioning
confidence: 99%
“…12), 该方法可应用于向复杂分子的 芳环引入三氟甲基(如 Estrone 和 Vitamin E 等). 2011 年, 清华大学刘磊教授 [42] 和北京大学的王剑 波教授等 [43] 发现在铜催化下, 亲电三氟甲基化试剂与 未活化的烯烃反应可生成三氟甲基化的烯丙基化合物 (Scheme 13), 他们对反应机理也进行了探索. [26] , Hartwig [21] 和 Gooβen 等 [25] 进一步开展硼酸和硼酯的氧化三氟甲基 化反应; 刘磊 [38] 、沈其龙 [39] 和肖吉昌等 [40] 研究了芳基硼 酸与亲电三氟甲基化试剂的反应.…”
unclassified